The Triple-S Advantage of Endoscopic Management in Gastrointestinal Surgery Complications: Safe, Successful, and Savings-Driven - Francesco Vito Mandarino; Emanuele Sinagra; Alberto Barchi; Silvio Danese (Life, 2024)
Despite advances in gastrointestinal (GI) surgery, post-operative complications are not entirely avoidable [...]